(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Pregnancy marks a significant milestone in a woman’s life, transitioning her from a woman to a mother. While it is a joyous journey, it brings about numerous physical and physiological changes that can lead to certain health challenges. Iron deficiency anemia is a prevalent health concern during pregnancy, particularly widespread in developing nations, necessitating urgent intervention to safeguard the lives of both the mother and the child. About 4 to 16% of maternal deaths are due to anemia. In contemporary science, to prevent complications like maternal and fetal mortality and morbidity, increased risk of infection, spontaneous abortion, intrauterine growth retardation, intrauterine death, premature delivery, low birth weight, postpartum hemorrhage etc during antenatal and postnatal period, various haematinic drugs are prescribed from 3rd month onwards. In Ayurveda this condition is considered as Garbhini Pandu. The Rasa and Rakta of the mother are carried to the fetus for its proper growth and development. If not, it leads to Rasa dhatu kshaya in Garbhini which finally leads to Garbhini Pandu. Ayurveda highlights the contradiction of Shodana in pregnant ladies, hence Shamana chikitsa can be followed judiciously. Considering the necessity of utilizing a safe and beneficial drug for Garbhini Pandu during pregnancy, certain indigenous drugs such as Agasthya, Amalaki, Draksha, Musta, Pippali, Sigru, Shuddha Kasisa, and Bhavana dravyas like Dadima, Bhringaraja, and Mandukaparni have been incorporated. This article highlights about the probable mode of action of indigenous drug formulation in Garbhini Pandu.